Log Chain, Nemaha County - Deters, Katelyn (Kansas State University, The Chapman Center for Rural Studies, 2010)
The town of Log Chain played an important role in one of the most famous mail carrying passages in the United States; however, when national factors such as the railroads were developed and the Pony Express died, Log Chain followed in close pursuit.
Katelyn Deters, “Log Chain, Nemaha County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/24.
Keywords: Albany; Civil War; Nemaha County; Pony Express Station; Log Chain; Granada